Urukskaya kul'tura Mesopotamii i Kavkaz - Muncaev, Rauf Magomedovic; Amirov, Sahmardan Nazimovic (History, Archeology and Ethnography of the Caucasus, 2007)
We decided to dedicate our report to the memory of the recently deceased outstanding Azerbaijani archaeologist Corr. Academy of Sciences of Azerbaijan Ideal Gamidoglu Narimanov. A graduate of the Leningrad University and a postgraduate student of the Institute of Archeology of the Academy of Sciences of the USSR, I.G. Narimanov, with his discoveries and works, made an invaluable contribution to the study of archeology, ancient history and culture of Azerbaijan, Transcaucasia and the Caucasus as a whole. For more than 10 years he was a member of the Mesopotamian Expedition of the Institute of Archeology of the USSR Academy of Sciences and participated in excavations of a whole group of early agricultural sites in Northwestern Iraq. And when in the early 80s. Ideal Narimanov discovered an Eneolithic settlement with an original ceramic complex and expressive architecture in the Karabakh steppe in Azerbaijan, he, as an experienced researcher, realized that this was not an ordinary monument characteristic of the Transcaucasian Eneolithic, but a settlement left by immigrants from Mesopotamia, more precisely by tribes - carriers of called Ubeid culture. This discovery and the conclusion made on the basis of its materials was, to a certain extent, sensational. And although in the future, for us, in particular, it became more obvious that this monument belongs not to the Ubeid, but to the Uruk culture following it, this does not significantly change the main fact - the fact of not just the influence of the ancient Mesopotamian culture on one of the adjacent regions, namely penetration into the South Caucasus in the 4th millennium BC. individual ethnocultural groups from the Middle East. We are talking about the settlement of Leyla-tepe - a monument now widely known to specialists and representing a separate culture of the Eneolithic of the South Caucasus.